Highly secured android apps based smart phone - Zhang, Yuzhou (2019)
Information exchange has always been an integral part of our daily lives. Some communicated information are confidential and need to be safe guard against the adversary. The Advanced Encryption Standard (AES) cipher algorithm is now widely used to secure highly-confidential information. It is still computationally infeasible to break the encrypted message stream. Side-channel attacks (SCA) have been used to reveal the secret keys which used for encryption and decryption the message by access to appropriate hardware. The most common and effective side-channel attack on AES is Differential Power Analysis (DPA). AES has been used in smart phone for data transmission especially for the applications like banking, live chat. This project will focus on the smart phone application based on Android smart phone and use different algorithm to protect the data to be transmitted and research the countermeasure against SCA in both hardware and software. The program designed as a data encrypt/decrypt application to show the enhanced data encrypt algorithm based on AES and compare the different cipher message for both encrypt algorithm and general AES algorithm. This program is more focus on the protection of the plaintext before AES encryption and the ciphertext after AES encryption.